Emotional and Behavioral Problems of Children with ASD-The Lessons That We Learned from the Pandemic - Margarita Stankova; Tsveta Kamenski; Ivan Ivanov; Polina Mihova (MDPI AG, 2023)
The data available for changes in the behavior and emotional state of children with ASD (autism spectrum disorder) in lockdown situations are controversial and scarce. In our research, we compare results before the first COVID-19 lockdown of 21 children with ASD and 21 typically developing children, four to five years of age with those obtained immediately after. The study attempts to answer the question of whether there are changes in the levels of emotional and behavioral problems in children with ASD after the lockdown and how these new living conditions affect some aspects of their functioning. The instruments used for data analysis are the Childhood Autism Spectrum Test (CAST); Child Behavior Checklist (CBCL); Survey on the consequences of COVID-19 on the life and development of the participants. No significant differences in the emotional and behavioral state of the participants were found, except for attention deficit/hyperactivity problems where ASD children showed lower levels after the lockdown. ASD group parents' answers to the survey pointed towards more positive consequences of staying at home. Some reported they had more time for learning together, communicating, playing, and assisting the learning process through online therapy. As negatives, the parents of ASD children reported low physical activity, increased time with electronic devices, and time spent with the same people. Caregivers of typically developing children agreed that the lockdown had only negative effects. To conclude, for children with ASD in the study, the lockdown period demonstrated that more time spent with parents in structured everyday activities is an opportunity that can lead to positive results in their behavior.